Preventing heat propagation and thermal runaway in electric vehicle battery modules using integrated PCM and micro-channel plate cooling system. (August 2019) - Kshetrimayum, Krishnadash S.; Yoon, Young-Gak; Gye, Hye-Ri; Lee, Chul-Jin
Highlights: Preventing heat propagation and thermal runaway for batteries in EVs and HEVs. Proposed integrated PCM and microchannel cooling plate system. CFD modeling of electrochemical, short-circuit and thermal runaway models. Effect of coolant flow configuration and coolant flow rate to prevent coolant boiling. Proposed cooling concept prevents thermal runaway for adjacent cells not subjected to nail penetration. Abstract: The effort to go entirely electric or increase portion of electric among automotive vehicle manufactures has grown significantly in the past few years. However, in the pursuit of this technological change, issues of battery overheating have also come to the forefront. For example, lithium-ion batteries of electric vehicles can lose thermal stability owing to mechanical damage such as nail penetration. A novel battery module thermal management method involving an integrated design of PCM and cooling plate has been proposed for preventing heat propagation and thermal runaway in a battery module made of 18, 650 cells that have been damaged by nail penetration of upto three cells. Intense heat generation of the order of 106 J/s under thermal abuse condition along with that of preceding nail penetration and normal discharge condition were obtained using Newman 2D pseudo electrochemical model, short-circuit model and thermal abuse model. Scenarios of upto 3 cells nail penetration were considered. For the case of 3 cells subjected to thermal abuse, when the water flow rate of 3.9 L min −1 and a counter-current flow was applied to two micro-channel plates, heat propagation to the adjacent cells was prevented. Maximum temperature of the cells adjacent to thermal abused cell was maintained below 363 K, thus preventing rest of the cells in the battery module from undergoing thermal runaway. At the used coolant volumetric flow rate, integrated cooling approach allowed keeping coolant temperature below its boiling point, thus helping in avoiding undesired situations of coolant boiling.